Limnanthes douglasii erucic acid-specific lysophospatidic acid acyltransferase activity in oilseed rape: an analysis of biochemical effects. (December 2000) - Wilmer, J. A.; Brown, A. P.; Forsyth, K.; Carnaby, S.; Barsby, T.; Slabas, A. R.
Abstract : It has been shown previously that erucic acid accumulates in the sn -2 position of triglycerides after introduction of a Limnanthes lysophosphatidic acid acyltransferase. However, in none of the studies to date has a proper evaluation been made of the relationship between transgene expression and the erucic acid accumulation at sn -2. One of the necessary tools to study the variability is the presence of a specific antibody raised against the introduced acyltransferase. In the present study, we have looked at the correlation between erucic acid accumulation at sn -2, production of trierucin and the expression of the transgene, as detected by Western blotting. The data presented include comparisons of progeny of individual lines grown under various conditions and at various times, and an analysis of a number of lines during development. We also present calculations that could indicate from which position the erucic acid found at position sn -2 is derived.